ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO KEUANGAN PADA PT. INDOSAT, Tbk YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Sutoro Sutoro; Arna Suryani; Evi Adriani (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2014)
This research aims to identify and analyze the company’s financial ratios seen from liquidity ratio (quick ratio, cash ratio, and inventory to net working capital), the solvency ratio (long-term debt to equity ratio), and activity ratio (receivable turnover, days of receivable, inventory turnover, days of inventory, working capital turnover, fixed asset turnover, and total assets turnover) as well as identify and analyze the financial performance of the company based on financial ratios at PT. Indosat, Tbk listed on Indonesia Stock Exchange period of 2009-2013. The results showed that only 3 out of 11 financial ratios (inventory turnover, days of inventory, and days of receivable) which showed positive results, meaning that the company has a good performance seen from the three analysis. While the rest showed that the company's performance poor. Such as the quick ratio with an average of 57.33%, cash ratio of 21.96%, inventory to net working capital of -1.53%, long-term debt to equity ratio of 128.74%, receivable turnover of 11.27 times, working capital turnover of 2.99 times, fixed assets turnover of 0.49 times, and total assets turnover of 0.39 times.